PENGARUH PEMEKARAN DAERAH TERHADAP DINAMIKA SOSIAL MASYARAKAT KOTA METRO TAHUN 2000-2019 - Sujarni Sujarni; Sumiyatun Sumiyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The research objective is to describe the effect of regional expansion on the social dynamics of the Metro City Society in 2000-2019. This research method is qualitative research, data and data sources obtained from books, government figures as sources, documentation, and other sources. The results of this study are: At the beginning of Metro City became a new autonomous region there has been a change in the Social Dynamics of the Community Like social control, there are two social controls namely Formal social control (school) non formal (religious institutions) and of course the role of social control institutions at the time it is experiencing problems because Metro City is still in a transitional stage or the development stage is a City. but over time the City of Metro is able to become more advanced in terms of formal and informal social control. Not only that, the Social Mobility of the City of Metro, such as work, has experienced a change, which in the beginning was the agricultural sector which became the main livelihood of the people of Metro City. switch to the service and trade sectors.